Manajemen Humas Pemerintah dalam Meningkatkan Kepercayaan Masyarakat - Syafari, Fairus Hayatus (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2014)
This discourse aims to describe that crisis of public trust on government can be improved by government public relations management with consistency of all government officials to communicate or portray themselves as public servants and above the public interest, and can ultimately achieve prosperous society development. Public relations management has not been optimal, there has been no organized effort from each agency to communicate government policies which are the main tasks and functions that must be carried out. This happens because of several aspects such as; (1) the low position of public relations in an agency and public relations are not treated as an important part for the agency (echelonization which is not directly under the leadership of the agency); (2) the absence of a strategic design and implementation of public relations programs to help leaders make decisions; (3) the lack of human resources capable of implementing government public relations programs; (4) the behavior of government officials is incompatible with the program / policy set by the government itself.